2015
DOI: 10.1093/treephys/tpv041
|View full text |Cite
|
Sign up to set email alerts
|

A state-space modeling approach to estimating canopy conductance and associated uncertainties from sap flux density data

Abstract: Uncertainties in ecophysiological responses to environment, such as the impact of atmospheric and soil moisture conditions on plant water regulation, limit our ability to estimate key inputs for ecosystem models. Advanced statistical frameworks provide coherent methodologies for relating observed data, such as stem sap flux density, to unobserved processes, such as canopy conductance and transpiration. To address this need, we developed a hierarchical Bayesian State-Space Canopy Conductance (StaCC) model linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…Sap flux of probe i at time t was modeled as Jit~N0.25em)(,Jt0.25emaiS, where J t is the average sap flux at time t , a i is the random effect associated with probe i , and S is the Gaussian observation variance. As opposed to the previous studies of trees using the StaCC model (Bell et al, ; Ward et al, ), we did not utilize a sapwood depth submodel due to the small sizes of stems (<7 mm) and a lack of information regarding radial reductions in sap flux. Similarly, because these small‐stemmed plants do not likely store an appreciable amount of stem water (Nobel & Jordan, ), we also did not utilize the additional capacitance submodel described in Bell et al ().…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sap flux of probe i at time t was modeled as Jit~N0.25em)(,Jt0.25emaiS, where J t is the average sap flux at time t , a i is the random effect associated with probe i , and S is the Gaussian observation variance. As opposed to the previous studies of trees using the StaCC model (Bell et al, ; Ward et al, ), we did not utilize a sapwood depth submodel due to the small sizes of stems (<7 mm) and a lack of information regarding radial reductions in sap flux. Similarly, because these small‐stemmed plants do not likely store an appreciable amount of stem water (Nobel & Jordan, ), we also did not utilize the additional capacitance submodel described in Bell et al ().…”
Section: Methodsmentioning
confidence: 99%
“…Next, G s,t was used to calculate actual canopy conductance ( G C ), assuming that G C is dependent on previous conductance and a time interval, d t (Rayment et al, ; Ward et al, ): GC=GCitalicdt+)(GstGCitalicdtVt, where d t = 30 min and V t = 1 − exp(− d t /τ) and τ is the stomatal lag in minutes. The V t term accounts for stomatal lags using a stomatal time constant ( τ ), where τ = 10 min, following Bell et al (). Canopy conductance was then used to calculate E L,t , (kg m −2 s −1 ) as EL,t=GCDt)(Tt273+144,600)(115.8+0.4226Tt, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5c-d). Synthesizing sap flow dynamics within a tree, for the whole tree, for groups of functionally related trees, and across the pantropical region enables improved understanding of ecohydrological processes in hyperdiverse tropical forests (Goldstein et al, 1998;Meinzer et al, 2001;Meinzer et al, 2004;Meinzer et al, 2005;Bell et al, 2015). The multiscale measurement position hierarchy facilitates such spatially extensive analyses because observations are defined by their position on the landscape and are linked by unique measurement position, tree (location), and site identifiers.…”
Section: Linking Complex and Diverse Observations Across Spatiotempormentioning
confidence: 99%
“…Monteith (1981) highlighted the fact that the biophysical conductances (i.e., gA and gC) regulating ET are heavily temperature dependent, after which a stream of research demonstrated the dominant control of TR into gC and associated canopy-scale aerodynamics (Moffett and Gorelick, 2012;Blonquist et al, 2009). Somewhat surprisingly, the idea of integrating TR into the PM model was never attempted because of complexities associated with gC 20 parameterization (Bell et al, 2015;Matheny et al, 2014), until the concept of STIC was formulated (Mallick et al, 2014;Mallick et al, 2015). The recent version of STIC, STIC1.2, combines PM with the Shuttleworth-Wallace (SW) model (Shuttleworth and Wallace, 1985) to estimate the source/sink height temperature and vapour pressure (T0 and e0) (Mallick et al, 2016).…”
Section: Et Mapping Is: How Can State-of-the-art Seb Models Overcome mentioning
confidence: 99%